Total Polyphenol, Rehydration Ratio, and Liquor Color of Different Grade Green Tea - M Iqbal Prawira-Atmaja; Beauty Azhary; Sugeng Harianto; Hilman Maulana; Shabri Shabri; Dadan Rohdiana (Jurnal Ilmu Pangan dan Hasil Pertanian, 2019)
Tea is a non-alcoholic beverage that is widely consumed after water with potential health benefits. In general, tea processing divided into three types, non-enzymatic oxidation process (green tea), semi-oxidation (oolong tea), and with enzymatic oxidation (black tea). The sorting and grading is a stage in controlling the quality of green tea. This study aims to determine the characteristics of different grades of green tea on the total polyphenols, liquor color, and rehydration ratio. The results showed that the pekoe/pecco grade had the highest total polyphenol and rehydration ratio compared to other grades. Pekoe grade has a greenish yellow  and brighter liquor color. Application of good agriculture practice (GAP) and plucking of fresh tea leaves should be considered to obtain more grade pekoe in the green tea processing.